IL‐4Rα on CD4+ T cells plays a pathogenic role in respiratory syncytial virus reinfection in mice infected initially as neonates. Issue 6 (29th March 2013) - You, Dahui; Marr, Nico; Saravia, Jordy; Shrestha, Bishwas; Lee, Greg I.; Turvey, Stuart E.; Brombacher, Frank; Herbert, DeˈBroski R.; Cormier, Stephania A.
Abstract : RSV reinfection increases IL‐4Rα expression on T helper cells, responsible for the enhanced immunopathologies in mice initially infected as neonates. Abstract : RSV is the major cause of severe bronchiolitis in infants, and severe bronchiolitis as a result of RSV is associated with subsequent asthma development. A biased Th2 immune response is thought to be responsible for neonatal RSV pathogenesis; however, molecular mechanisms remain elusive. Our data demonstrate, for the first time, that IL‐4Rα is up‐regulated in vitro on human CD4 + T cells from cord blood following RSV stimulation and in vivo on mouse pulmonary CD4 + T cells upon reinfection of mice, initially infected as neonates. Th cell‐specific deletion of Il4ra attenuated Th2 responses and abolished the immunopathophysiology upon reinfection, including airway hyper‐reactivity, eosinophilia, and mucus hyperproduction in mice infected initially as neonates. These findings support a pathogenic role for IL‐4Rα on Th cells following RSV reinfection of mice initially infected as neonates; more importantly, our data from human cells suggest that the same mechanism occurs in humans.